Impact localization on composite structure using FBG sensors and novel impact localization technique based on error outliers. (10th May 2016) - Shrestha, Pratik; Kim, Jin-Hyuk; Park, Yurim; Kim, Chun-Gon
Abstract: Structural health monitoring of composite structures is essential for timely detection and localization of low velocity impacts. In this paper, a novel method for localizing impacts using an error outlier based impact localization algorithm is proposed. The outlier method for impact localization was developed and implemented by localizing several impact points on a quasi-isotropic composite structure. Multiplexed FBG sensors were attached to the composite structure to monitor low velocity impacts, sampled at a frequency of 100 kHz using a high speed FBG interrogator. Localization results for the error outlier based localization method were compared with the RMS and correlation based impact localization results. The novel localization technique presented in this paper demonstrates an effective means of estimating impact locations. Furthermore, overall improvement in the localization performance was obtained using the outlier based impact localization algorithm: impact points on the composite plate were localized with an average error of 10.7 mm.